Pathogenicity of infectious bronchitis virus isolate of Malaysia in specific pathogen free chicken - Mardiyah M. Nasir.
Infectious bronchitis (IB) is one of very important disease in chicken. It caused by IB virus (IBV) from Coronaviridae family. This disease is a worldwide, acute and highly contagious disease. The virus easily changes in nature and emerges as new strain and cause a lot of problem. In Malaysia, the nephrogenic strain was detected since 1995 and the new variant QX strain was reported recently in 2009. These 2 types of strain caused high mortality and loss of production. Hence, the objectives of this study were to isolate and identify IBV from chickens during field outbreak of the disease in 2009 and determine the clinical signs, gross and histological lesions of specific pathogen free (SPF) chicken infected with the IBV isolate. Samples of lung, kidney and trachea from suspected IB were tested for reverse transcriptase polymerase chain reaction (RT-PCR) and then inoculated to 10-day-old SPF embryonated chicken eggs via allantoic route for virus isolation, propagation and preparation of the IBV inoculums. The allantoic fluid and chorioallantoic membranes (CAM) from the inoculated eggs then were tested for the presence of IBV before inoculated into SPF chicken. Seventy two, day-ole SPF chicken were divided into 3 groups known as groups A, B and C. Groups A and B were inoculated with IBV inoculums 0.1ml via intranasal route while group C remained as uninoculated and serve as control group. Four chickens were sacrificed prior to IBV inoculation. At days 1, 3, 5, 7, 14 and 21 post inoculation (pi), four chickens from group A and C were sacrificed. The bodyweight was collected prior to sacrifice. On necropsy, gross lesions were recorded and samples of trachea and kidney were collected and fixed in 10% buffered formalin for histological examination. Mortality and any abnormal clinical signs were recorded at least twice a day. Feed and drink were given ad libitum. The results showed that IBV was successfully detected from the trachea, lung and kidney samples of the chickens from field outbreak by RT-PCR. IBV also was successfully isolated and propagated in SPF embryonated chicken eggs and detected in the allantoic fluids and CAM. The pathogenicity study showed that the IBV isolate caused severe respiratory signs and high mortality (60%) up to day 14 pi. Mild to severe gross and histological lesions were recorded in the trachea and kidney up to day 14 pi. However, signs of recovery with mild respiratory sign, absence of mortality and mild kidney lesions were recorded at 21 pi. It was concluded that the IBV isolate is highly pathogenic and might be a new emerging strain or variant strain of IBV.